Management of root-knot nematode Meloidogyne hapla on strawberry plant with some plant extracts - H. . Samaliev; D. . Markova; M. . Nikolova; O. . Baicheva (Российский паразитологический журнал)
The activity of alcohol extracts from 6 plant species was investigated with respect to the root-knot nematode-strawberry system. An evaluation was made of the nematostatic and nematicidal activity of the extracts. In production conditions, the most active was the extract Tanacetum vulgare at concentration 0.6%. It had the lowest M. hapla population density, with gall index and root/soil population densities not different than the oxamil treated plants and there were no stastically proved difference between T. vulgare and non-infested control.